ANALISIS PENGARUH DISTANT LEADERSHIP TERHADAP EMPLOYEE ENGAGEMENT DALAM PENINGKATAN KINERJA FAKULTAS BISNIS UNIVERSITAS UNIVERSAL DENGAN METODE LATENT DIRICHLET ALLOCATION - Kurniawan, Wiky; Pradana, Mochammad Nugraha Reza (Fortunate Business Review, 2022)
The key to increasing employee engagement is leadership. Several studies have shown that remote leadership has a positive effect on companies. Other studies also reveal that direct leadership is better applied to improve the company's positive performance. The purpose of this study was to determine the role of remote leadership for improving organizational performance on the object of research. The object of this research is the business faculty of Universal University. This type of research is qualitative research that uses topic modeling Latent Dirichlet Allocation (LDA) to find out the topic of discussion on important topics. This study utilizes the technique of collecting data from direct interviews with six sources including leaders and employees who have experience working remotely in the business faculty. The results of the study show that remote leadership, remote work environment, and the use of digital collaboration tools show important roles that can influence employee engagement in implementing remote work in business schools in order to improve faculty performance.